Oil Price Shock and Agricultural Productivity: Stylised Evidence in Nigeria - Popoola, Olabisi; Philip, Alege O.; Gershon, Obindah; Gift, Kaladede (International Journal of Energy Economics and Policy, 2022)
Oil sector is a dominant sector, as it is the largest exported commodity in Nigeria. However, evidences have shown that Nigeria as an oil dependent country faces frequent oil price fluctuations that have pose greater challenge on agriculture sector in Nigeria, hence affecting agricultural productivity. This necessitates the need to investigate the effect of oil price shocks on agricultural productivity in Nigeria. This study adopted the Hodrick Prescott data filtering approach to check for the fluctuation of oil price. The result revealed fluctuation in Nigeria oil price from 2018 up until recently. Also, the Structural Vector Autoregression and normalized equation was used to establish the long-run equation. Evidence from the long-run relationship showed that agricultural productivity has a negative relationship with oil price and real exchange rate. Consumer price index, and oil production has as positive relationship with agricultural productivity. Variation in oil price affects most of the variables. However, oil price shock shows more variations across the time for agricultural productivity. To this end, this study revealed that oil price shock has adverse effect on agricultural productivity in Nigeria. Hence, the need for the government to implement a policy and programmes that will serve as oil price shock absorber in order to sustain agricultural productivity.